Cardiovascular Risk Factors in Adolescents with Type 1 Diabetes: Prevalence and Gender Differences - Doğuş Vurallı; Lala Jalilova; Ayfer Alikaşifoğlu; Z. Alev Özön; E. Nazlı Gönç; Nurgün Kandemir (JCRPE, 2024)
INTRODUCTION: Cardiovascular diseases (CVD) are the most important cause of morbidity and mortality in patients with type 1 diabetes (T1D). Children with T1D have a similar or higher prevalence of being overweight (OW) or obese (Ob) compared to healthy peers. The aim of this study was to determine the prevalence of CVD risk factors in children and adolescents with T1D and the impact of obesity and sex differences on these factors. METHODS: Data of patients aged 10-21 years and who had been using intensive insulin therapy with a diagnosis of T1D for at least three years were evaluated. Patients were divided into normal weight (NW), OW and Ob groups based on body mass index percentiles. Risk factors for CVD (obesity, dyslipidemia, hypertension) were compared between groups, and impact of gender was also analyzed. RESULTS: Data of 365 patients (200 girls, 54.8%), were evaluated. Prevalence of OW/Ob was 25.9% and was significantly higher in girls (30.6% vs 20.1%, p<0.001). Rate of hypertension was highest in OW/Ob girls followed by OW/Ob boys, and similar in NW girls and boys (p=0.003). Mean low density lipoprotein cholesterol (LDL-c) and triglyceride (TG) levels were highest in OW/Ob girls, followed by OW/Ob boys, NW girls and NW boys, respectively (p<0.001 and p<0.001, respectively). Mean high density lipoprotein-cholesterol (HDL-c) levels were similar among groups. Rates of high LDL-c and TG were similar between OW/Ob girls and boys and higher than NW girls, followed by NW boys (p<0.001 and p<0.001, respectively). The rate of low HDL-c was similar in OW/Ob girls and boys, and higher than NW girls, followed by NW boys (p<0.001). Overall, girls were 1.9 times more likely than boys to have two or more risk factors for CVD. Factors associated with risk for CVD in multiple logistic regression analyses were being a girl, followed by higher daily insulin dose, higher hemoglobin A1c, and longer duration of diabetes (r=0.856; p<0.001). DISCUSSION AND CONCLUSION: In spite of the increased prevalence for obesity in both sexes, the trend for CVD risk factors was greater in Ob girls, followed by Ob boys and NW girls. Girls with T1D are more likely to be OW/Ob and to have CVD risk than boys, highlighting the need for early intervention and additional studies to elucidate the causes.